The Role of The Teacher in Promoting The Culture of Islamic Tolerance Among Tenth-Grade Students in Jordan From The Students’ Point of View - Alazeez, Amjed Mohammad Alabd; AL-Momani, Mohammad Omar; Rababa, Elham Mahmoud (Nazhruna: Jurnal Pendidikan Islam, 2024)
The study aims to identify the role of the teacher in promoting the Islamic culture of tolerance among tenth-grade students in Jordan by keeping in view the relationship of tolerance to the variables of gender and place of residence. To achieve the objectives of the study, the descriptive approach has been used, in addition to using the questionnaire as a tool for the study which was applied to a sample consisting of two thousand male and female students studying in the second semester of the academic year (2023-2024). The results of the study show that twelve (12) items obtained a score of (very high), and sixteen (16) items obtained a score of (high). It has been observed that the role of the teacher in promoting the culture of tolerance among tenth-grade students was high on the scale as a whole, in addition to the presence of statistically significant differences between the students’ opinions according to the variables of gender, in favor of males and place of residence, and favor of students in rural areas and villages.